2019
DOI: 10.1155/2019/7404038
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Cytotoxicity of Self-Adhesive Dual-Cured Resin Cement Polymerized Beneath Three Different Cusp Inclinations of Zirconia

Abstract: The aim of the present study was to evaluate the in vitro cytotoxicity of self-adhesive dual-cured resin cement (SADRC) polymerized beneath three different cusp inclinations of zirconia with different light curing time. A commercial SADRC (Multilink Speed) was polymerized beneath zirconia (ZrO2) with three different cusp inclinations (0°, 20°, and 30°) for 20 s or 40 s. After being stored in light-proof box for 24 h, the ZrO2-SADRC specimens were immersed in DMEM for 72 h and then we got the extract solution, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…It should be noted that there was a significant reduction in cell viability in the TPP-10 group on day 7 compared with the negative control. However, the cell viability of the TPP-10 group at day 7 was nearly 75% relative to the negative control, which means that it was acceptable for cell proliferation according to the biological Evaluation Standards of Medical Devices of China (GB/T16886.5.2003). , All these results demonstrated that telmisartan-loaded PCL/PVP scaffolds had good biocompatibility and were feasible for further functional evaluation.…”
Section: Resultsmentioning
confidence: 81%
“…It should be noted that there was a significant reduction in cell viability in the TPP-10 group on day 7 compared with the negative control. However, the cell viability of the TPP-10 group at day 7 was nearly 75% relative to the negative control, which means that it was acceptable for cell proliferation according to the biological Evaluation Standards of Medical Devices of China (GB/T16886.5.2003). , All these results demonstrated that telmisartan-loaded PCL/PVP scaffolds had good biocompatibility and were feasible for further functional evaluation.…”
Section: Resultsmentioning
confidence: 81%
“…It contains WST‐8, a water‐soluble tetrazolium salt, which, in viable cells, is reduced to a colored formazan dye by dehydrogenase activity (Ishiyama et al, 1997 ). It represents a well‐established and reproducible method for the quantification of cell viability and cell proliferation (Camassa et al, 2021 ; Schubert et al, 2019 ; Zhang et al, 2019 ; Zhu et al, 2019 ), and it is more sensitive than other colorimetric assays (Failli et al, 2013 ; Miyamoto et al, 2002 ).…”
Section: Discussionmentioning
confidence: 99%
“…The remaining 29 articles [1][2][3][4][5][6][7][8][9][10]14,22,[25][26][27][28]31,[33][34][35][36][37][38][39][40][41][42][43][44] were selected for the quality analysis. Manual research also retrieved three studies [30,45,46], three randomized clinical trials [24,47,48], six reviews [15,23,29,[49][50][51], and three meta-analyses [11,12,20], which were used to broaden the introduction and discussion sessions. The selection process agreed with the PRISMA Statement, as shown in Figure 1.…”
Section: General Aspectsmentioning
confidence: 99%
“…Despite being more straightforward, professionals must know that problems can occur during cementation with SARC. Lack of polymerization efficiency, with the potential release of unreacted cytotoxic and genotoxic monomers [30], induces expansion of the cement layer, with polymerization shrinkage strain and high stresses caused by hygroscopic expansion, with possible crack formation and restoration failure [26,28]. An evenly distributed cement layer with low internal gap values is essential for correct seating and better mechanical properties, but also for a low-space volume of the cement and porosities inside the luting agent [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation